New techniques and methods for prevention and treatment of symptomatic traumatic neuroma: A systematic review - Zhou, Liping; Huo, Tong; Zhang, Wenmin; Han, Na; Wen, Yongqiang; Zhang, Peixun (Frontiers in Neurology, 2023)
Generally, axons located at the central end of the nerve system will sprout after injury. Once these sprouts cannot reach the distal end of the severed nerve, they will form a traumatic neuroma. Traumatic neuromas bring a series of complex symptoms to patients, such as neuropathic pain, skin abnormalities, skeletal abnormalities, hearing loss, and visceral damage. To date, the most promising and practical clinical treatments are drug induction and surgery, but both have their limitations. Therefore, it will be the mainstream trend to explore new methods to prevent and treat traumatic neuroma by regulating and remodeling the microenvironment of nerve injury. This work first summarized the pathogenesis of traumatic neuroma. Additionally, the standard methods of prevention and treatment on traumatic neuroma were analyzed. We focused on three essential parts of advanced functional biomaterial therapy, stem cell therapy, and human-computer interface therapy to provide the availability and value of preventing and treating a traumatic neuroma. Finally, the revolutionary development of the prevention and treatment on traumatic neuroma has been prospected. How to transform the existing advanced functional materials, stem cells, and artificial intelligence robots into clinical practical technical means as soon as possible for high-quality nerve repair and prevention of neuroma was further discussed.